2018
DOI: 10.1249/01.mss.0000535931.19316.91
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Lifestyle Intervention on Change in Body Composition in Prostate Cancer Patients Undergoing Androgen Deprivation Therapy

Abstract: Background Exercise and dietary (EX+D) interventions could represent an optimal treatment for attenuating or reversing adverse effects of androgen deprivation therapy (ADT) in prostate cancer (PCa) patients. The Individualized Diet and Exercise Adherence-Pilot (IDEA-P) trial compared the effects of an EX+D intervention relative to standard-of-care (SC) treatment among PCa patients undergoing ADT. The present study evaluated the effects of the EX+D intervention on body composition (BC) obtained via dual-energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Together, these constructs have been shown to predict functional decline [ 8 ], mediate the beneficial effects of lifestyle interventions upon mobility performance [ 5 , 9 ], and are key aspects of one’s agency to pursue goal-directed actions that are integral to successful adoption and maintenance of lifestyle behavior change in older adults with, or at risk, for mobility disability [ 10 12 ]. Consistent with these findings, results from our recently completed Individualized Diet and Exercise Adherence-Pilot (IDEA-P) trial demonstrate that a Social Cognitive Theory-based lifestyle exercise and dietary intervention yielded improvements in body composition, functional, and social cognitive outcomes relative to standard of care treatment in PCa patients on ADT [ 5 , 6 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…Together, these constructs have been shown to predict functional decline [ 8 ], mediate the beneficial effects of lifestyle interventions upon mobility performance [ 5 , 9 ], and are key aspects of one’s agency to pursue goal-directed actions that are integral to successful adoption and maintenance of lifestyle behavior change in older adults with, or at risk, for mobility disability [ 10 12 ]. Consistent with these findings, results from our recently completed Individualized Diet and Exercise Adherence-Pilot (IDEA-P) trial demonstrate that a Social Cognitive Theory-based lifestyle exercise and dietary intervention yielded improvements in body composition, functional, and social cognitive outcomes relative to standard of care treatment in PCa patients on ADT [ 5 , 6 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 69%
“…It is notable that recent evidence demonstrated that improved mobility performance following a weight management intervention was more strongly associated with reductions in total body mass, driven primarily by loss of fat mass, rather than enhanced muscular strength [ 4 ]. We previously demonstrated that the EX+D intervention in IDEA-P resulted in significant improvements in mobility, muscular strength, and body composition in PCa patients on ADT and that improvements in adiposity were more strongly related to mobility performance while the lean mass outcomes were more consistently associated with muscular strength [ 6 , 13 , 14 ]. Collectively, these results underscore the importance of exploring how interactions among change in multiple facets of body composition and social cognitive constructs may contribute to optimizing intervention strategies, personalizing approaches to individuals, and maximizing improvements in mobility performance accompanying lifestyle interventions among PCa patients on ADT in future inquiry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations